Good luck, have fun, don't die [videorecording (DVD)] - Zanelli, Geoff, 1974- (Universal, 2026)
"A man claiming to be from the future recruits an unlikely group of diner patrons to join him on a genre-defying adventure to save humanity from the perils of social media brainrot and the impending AI apocalypse!"--